Effect of Dimeticone and Pepsin on the Bioavailability of Metoclopramide in Healthy Volunteers - do Nascimento, D. F.; Silva Leite, A. L. A. e; de Moraes, R. A.; Camarão, G. C.; Bezerra, F. A. F.; de Moraes, M. O.; de Moraes, M. E. A. (Drug Research, 2014)
To assess the effect of dimeticone and pepsin on the bioavailability of metoclopramide (CAS 7232-21-5) in healthy volunteers.The study was conducted using a randomized, open, 2-period crossover design. The volunteers received single administration of 7-mg conventional metoclopramide capsule and a formulation containing metoclopramide (7 mg) plus dimeticone (40 mg) and pepsin (50 mg), with a 7-day interval between treatments. Serial blood samples were collected before dosing and during 24 h post-treatment. Plasma metoclopramide concentrations were analyzed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). The pharmacokinetics parameters AUClast and Cmax were obtained from the metoclopramide plasma concentration vs. time curves.Metoclopramide’s association was bioequivalent to conventional capsule; 90% CIs for geometric mean treatment ratios of Cmax [108.0% (90% CI, 100.4–116.3%)], AUClast [103.3% (90% CI, 99.5–107.4%)] were within the predefined range. The metoclopramide formulations were well tolerated at the administered doses and no significant adverse reactions were observed. Thus, these results confirm the good bioavailability of metoclopramide in the new formulation and rule out any impaired absorption when the drugs are formulated in combination.
Keywords: metoclopramide; bioavailability; pharmacokinetic; LC-MS/MS; clinical trial